2003
DOI: 10.1136/bjo.87.10.1220
|View full text |Cite
|
Sign up to set email alerts
|

Automated identification of diabetic retinal exudates in digital colour images

Abstract: Aim: To identify retinal exudates automatically from colour retinal images. Methods: The colour retinal images were segmented using fuzzy C-means clustering following some key preprocessing steps. To classify the segmented regions into exudates and non-exudates, an artificial neural network classifier was investigated.Results: The proposed system can achieve a diagnostic accuracy with 95.0% sensitivity and 88.9% specificity for the identification of images containing any evidence of retinopathy, where the trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(94 citation statements)
references
References 3 publications
0
93
0
1
Order By: Relevance
“…We found that EXs appear most contrasted in the green channel, and optic disc appears most continuous and most contrasted against the background in the red channel [19]. So we coarsely segmented EXs in the green channel as shown in Figure 2(a), and segmented optic disc in the red channel which was EXs Optic disc shown in Figure 2(b).…”
Section: Improved Otsu Thresholding Segmentation Stagementioning
confidence: 99%
“…We found that EXs appear most contrasted in the green channel, and optic disc appears most continuous and most contrasted against the background in the red channel [19]. So we coarsely segmented EXs in the green channel as shown in Figure 2(a), and segmented optic disc in the red channel which was EXs Optic disc shown in Figure 2(b).…”
Section: Improved Otsu Thresholding Segmentation Stagementioning
confidence: 99%
“…The four main vessels originating from the OD were geometrically modeled using two parabolas, and the OD position was located as their common vertex. Inspired by previous works, Youssif et al [6]. The OD center location was identified using the variance of intensity produced by the blood vessels within the OD.…”
Section: Overview Of Papermentioning
confidence: 99%
“…In a clustering technique along with the region growing, each pixel is associated with one of the finite number of threshold is grown to form disjoint regions. The contextual clustering method proposed by [4,9] is a supervised algorithm. It uses a 3 X 3 overlapping windows of pixels to form a segmented image.…”
Section: Esnn With Region Growingmentioning
confidence: 99%